The axiom of choice in the papers of Wacław Sierpiński - Lewandowska, Katarzyna (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2013)
This paper presents Wacław Sierpiński – the first advocate of the axiom of choice. We focus on the philosophical and mathematical topics related to the axiom of choice which were considered by Sierpiński. We analyze some of his papers to show how his results effected the debate over Zermelo’s axiom. Sierpiński’s impact on this discussion is of particular importance since he was the first who tried to explore consequences of the axiom of choice thoroughly and asserted its undoubted significance to mathematics as a whole.